Income Inequality and Economic Growth Revisited. A Note. (18th August 2017) - Caraballo, Mª. Ángeles; Dabús, Carlos; Delbianco, Fernando
Abstract: The relationship between income inequality and economic growth is estimated using dynamic panel estimation on a sample covering 112 emerging countries for the period 1980–2014. The results show that income inequality has a positive influence on economic growth for richer countries, in line with the classic theory, and a negative effect for poorer countries, as argued by the political economy approach. Copyright © 2017 John Wiley & Sons, Ltd.